Nitrogen Fertilization Effects on Oil Content, Sucrose, α- Tocopherol, Fatty Acid and Aminoacid Compositions of Confectionary Sunflower Seed - Öner Canavar; Hatice Kübra Gören (Journal of Agricultural Sciences)
This study investigates the effects of nitrogen fertilization on the composition of confectionary sunflower seeds, including parameters such as oil content, alpha-tocopherol, sucrose, amino acids and fatty acid composition. Nitrogen fertilization, surprisingly, had no significant effect on sunflower oil content, with remarkable differences observed between the genotypes. The α-tocopherol content, an important antioxidant, displayed responses that were dependent on the genotype upon application of nitrogen. The Somon Beyazı genotype consistently demonstrated higher oil content compared to the Ahmet Bey genotype. In addition, both genotypes showed a decrease in α-tocopherol levels as the application of nitrogen increased. Sucrose content was higher in the Somon Beyazı genotype and decreased significantly with increasing nitrogen doses. Significant variations were observed in fatty acid compositions, further emphasizing the impact of genotype and nitrogen application. The study also revealed diverse amino acid profiles, with notable concentrations of glutamine and asparagine. This comprehensive study highlights the complex interaction between genotype and nitrogen fertilization and provides valuable insights for optimising sunflower seed production and quality. The results emphasise the significance of integrating both genetic factors and nutrient management practices into crop cultivation for improved agricultural outcomes.